Necessary English Competencies in Oral Communication for Business Administration Graduates to Work Effectively: A Workplace Reflection - Tram, Nguyen Thi Minh (VNU Journal of Foreign Studies, 2016)
Abstract: The issue that Vietnamese business administration (BA) graduates” competences in oral communication in English are inadequate to meet the real workplace requirements has been increasingly urgent to be considered especially since Vietnam”s accession into the World Trade Organization (WTO) and Trans-Pacific Partnership (TPP). This emphasizes the necessity of exploring necessary English competencies in oral communication that BA graduates need to work effectively in the demanding market. In the present research, both quantitative and qualitative data were collected in a mixed methods study, in which various sources of participants including BA graduates fromForeign Trade University,Vietnam University of Commerce andNationalEconomicsUniversity, and their employers at workplace involved. Keywords: Oral communication in English, business administration, competences.